Tropical wild fern (Diplazium esculentum) as a new and effective low-cost adsorbent for removal of toxic crystal violet dye. Issue 1 (1st January 2020) - Lim, Linda B. L.; Usman, Anwar; Hassan, Muhammad Hanif; Mohamad Zaidi, Nur Afiqah H.
Abstract : A tropical wild fern, Diplazium esculentum, locally known as Pakis, was investigated in this study as a low-cost adsorbent for the removal of toxic crystal violet (CV) dye. The adsorbent–adsorbate system reached equilibrium in 180 min and data obtained from batch adsorption experiment were best fitted with the Sips isotherm model. High maximum adsorption capacity ( q max ) of 350.86 mg/g compared to many other reported adsorbents revealed the potential of this fern as a low-cost, new adsorbent for the removal of CV. Adsorption mechanism followed the pseudo second-order kinetics. Another attractive feature is its ability to be regenerated and reused, especially when using the base treatment, while maintaining high adsorption of >96% even at the fifth consecutive cycles.